Determinants of, and the Relation Between, Foreign Direct Investment and Growth : A Summary of the Recent Literature - Lim, Ewe-Ghee (IMF Working Papers; Working Paper, 2001)
This paper summarizes recent arguments/findings on two aspects of foreign direct investment (FDI): its correlation with economic growth and its determinants. The first part focuses on recent literature regarding positive spillovers from FDI while the second deals with the determinants of FDI. The paper finds that while substantial support exists for positive spillovers from FDI, there is no consensus on causality. On determinants, the paper finds that market size, infrastructure quality, political/economic stability, and free trade zones are important for FDI, while results are mixed regarding the importance of fiscal incentives, the business/investment climate, labor costs, and openness.